Tea polyphenol-inspired tannic acid-treated polypropylene membrane as a stable separator for lithium–oxygen batteries. Issue 25 (19th June 2017) - Wu, Chaolumen; Li, Taoran; Liao, Chenbo; Li, Lei; Yang, Jun
Abstract : Tannic acid, one of the most common tea polyphenols, is a superoxide radical scavenger that is coated on the PP membrane to protect it from being attacked by superoxide radicals during the discharging and charging process of the Li–O2 battery. Abstract : Tannic acid, one of the most common tea polyphenols, is a superoxide radical scavenger that is coated on the PP membrane to protect it from being attacked by superoxide radicals during the discharging and charging process of the Li–O2 battery. The radical scavenging capability of TA was evaluated in both KO2 + crown solution and Li–O2 battery and the effective superoxide radical scavenging ability of TA was confirmed; moreover, due to this ability, it highly improved the cycling stability of the Li–O2 battery.